HAND BURNS– TYPES, HELPS (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
Hand burns are very common. Burns often occur while doing routine household chores. It can be laundry, cooking or ironing. The most important thing is to know what to do in the first seconds when your hand burns. First aid methods for burns mainly depend on its cause.